Characterization of group II chaperonins from an acidothermophilic archaeon Picrophilus torridus. Issue 7 (14th June 2016) - Yamamoto, Yohei Y.; Tsuchida, Kanako; Noguchi, Keiichi; Ogawa, Naoki; Sekiguchi, Hiroshi; Sasaki, Yuji C.; Yohda, Masafumi
Abstract : Chaperonins are a type of molecular chaperone that assist in the folding of proteins. Group II chaperonins play an important role in the proteostasis in the cytosol of archaea and eukarya. In this study, we expressed, purified, and characterized group II chaperonins from an acidothermophilic archaeon Picrophilus torridus . Two genes exist for group II chaperonins, and both of the gene products assemble to form double‐ring complexes similar to other archaeal group II chaperonins. One of the Picrophilus chaperonins, PtoCPNα, was able to refold denatured GFP at 50 °C. As expected, PtoCPNα exhibited an ATP‐dependent conformational change that is observed by the change in fluorescence and diffracted X‐ray tracking (DXT). In contrast, PtoCPNα lost its protein folding ability at moderate temperatures, becoming unable to interact with unfolded proteins. At lower temperatures, the release rate of the captured GFP from PtoCPNα was accelerated, and the affinity of denatured protein to PtoCPNα was weakened at the lower temperatures. Unexpectedly, in the DXT experiment, the fine motions were enhanced at the lower temperatures. Taken together, the results suggest that the fine tilting motions of the apical domain might correlate with the affinity of group II chaperonins for denatured proteins. Abstract : A group II chaperonin of the acidothermophilic archaeon, Picrophilus torridus (PtoCPNα), exhibits ATP‐dependent conformational change and protein folding activity at 50 °C. But, PtoCPNα has lost the ability to interact with unfolded proteins. Diffracted X‐ray tracking experiment showed that the fine tilting motions of the apical domain might correlate with the affinity of group II chaperonins to denatured proteins.